2020
DOI: 10.1016/j.resconrec.2020.105016
|View full text |Cite
|
Sign up to set email alerts
|

Circular economy as a COVID-19 cure?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 3 publications
1
70
0
Order By: Relevance
“…This ability and commitment for open global collaboration and mutual learning is described as one of the unique features of the global maker movement ( Smith, 2017 ) and also implies a certain ethical commitment of the contributing makerspaces. The cases contributing to this study confirm their potential for empowerment as suggested by ( Avelino et al, 2019 ) and resilience of the local actors, similar to what has been encountered by Wuyts et al (2020) .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This ability and commitment for open global collaboration and mutual learning is described as one of the unique features of the global maker movement ( Smith, 2017 ) and also implies a certain ethical commitment of the contributing makerspaces. The cases contributing to this study confirm their potential for empowerment as suggested by ( Avelino et al, 2019 ) and resilience of the local actors, similar to what has been encountered by Wuyts et al (2020) .…”
Section: Discussionsupporting
confidence: 79%
“…Smith, 2017;Richterich, 2020). Wuyts et al (2020) likewise recognize the value of maker activities during the pandemic in moving towards a more circular economy in the healthcare sector.…”
Section: Discussionmentioning
confidence: 99%
“…Since the declaration of coronavirus infectious disease 19 (COVID-19) as a global pandemic (WHO 2020a), its progression in countries around the world has been rapid and the daily reported statistics of the cases and casualties have been alarming (MacKenzie, 2020; Worldometers, 2020 ; WHO 2020b). Notably, the effects of this pandemic have greatly impacted the social, economic, health, education, environmental and tourism sectors of society ( AWWA, 2020 , Fine et al, 2020 ; CCSA, 2020; Wuyts, et al 2020 ). In the last few months, one of the areas where the environmental impacts of COVID-19 are most pronounced is in waste management ( Klemeš et al, 2020 , Nzediegwu and Chang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic can serve as a constructive change driver for sustainability and future resilience, but also as a challenge for adopting CE strategies in face of a scenario with accelerated municipal and hazardous waste generation rates (Wuyts et al 2020). The results of the present study illustrate the challenges of implementing comprehensive CE policies in a post-COVID-19 era and the need to measure its progress, contribution to sustainable development and to the economic reactivation and green recovery.…”
Section: Discussionmentioning
confidence: 83%